Lippincott's illustrated Q&A review of microbiology & immunology - Buxton, B. A. (Bonnie A.) .); Gregg, Randal K.; Jensen, Lauritz A (Philadelphia : Wollters Kluwer Health/Lippincott Williams & Wilkins, 2010)
The book is heavily illustrated with photos of clinical manifestations or of gram-stained organisms, parasite eggs, oocysts or other parasitic stages, or pathologic specimens.Online access to the questions and answers provides flexible study options. And cover frequently tested topics in bacteriology, virology, mycology, parasitology, infectious disease, basic immunology, and clinical immunology
Bacteriology -- Virology -- Mycology -- Parasitology -- Infectious disease -- Basic immunology -- Clinical immunology
Includes index
Includes bibliographical references and index
13
Keywords: Microbiology -- Examinations, questions, etc; Microbiology -- Outlines, syllabi, etc